Possible Implications of Integrating the Corporate and Individual Income Taxes in the United States. (IMF Working Papers; Working Paper, 1990)
The classical corporate profits tax in the United States involves non-neutralities between: different sources of financing; different forms of business organization; and retaining or distributing earnings and may result in the U.S. investor being at a disadvantage vis-a-vis foreign investors. An international comparison is provided, and the potential effects of different integration schemes on the user cost of capital and tax revenues are assessed. The integration of corporate and individual income taxes in the United States could lead to a more efficient domestic and worldwide allocation of resources.